Videophotometric velocimeter using temporal cross-correlation. - Sison, Luis G.
Frame-by-frame analysis is the most established and accurate technique for measuring blood flow in microcirculation using videophotometry. Automated analysis software such as Capiflow, which are based on temporal cross-correlation, have been shown to have no significant difference in measured velocity compared to frame-by-frame analysis. However, these comparative studies did not investigate the causes and models of possible failure in the temporal cross-correlation algorithm, nor did they study the effect of gross subject motion. In this first of a series of reports, we show that the temporal cross-correlation algorithm applied to single-point intensities typically yield errors of less than 3 frames. However, significant error may result when the intensity history does not have significant variation during the time periods of interest, or when there is a significant background difference between the selected start and end points.
Keywords: Digital image processing; Microcirculation; Velocimeter; Videophotometry